DETERMINAN OF CAESAREAN SECTION IN PRIMIGRAVIDAE: CASE CONTROL STUDY 2017-2019 - Fithriyah, Noor; Widiasih, Restuning; Solehati, Tetti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Caesarea Section (CS) delivery causes short and long term complications, as well as death that can occur during intraoperative, post-operative, or subsequent pregnancies. Many studies have been conducted on the causes of cesarean delivery, but research on the factors that cause cesarean delivery is still limited, especially in primigravidas. Primigravidas have a higher risk of experiencing CS related to the physical and psychological condition of the mother. This study aims to analyze the factors that cause cesarean delivery in primigravida. A retrospective case control study at Idaman Hospital was conducted in October – November 2020 with research ethics number 466/UN6.KEP/EC/2021. Data was collected from the medical records of 588 primigravidas divided into SC (n=294) and normal (294) deliveries between 2017-2019. Data were analyzed using chi square and logistic regression. The results of the analysis showed that there was a relationship between labor induction (p=0.000), prolonged labor (p=0.001), premature rupture of membranes (p=0.001), cephalopelvic disproportion (CPD) (p=0.000), and umbilical cord entanglement (p= 0.048) with faults in primigravida. The most correlated multivariate factor was CPD Exp (B) = 18.741. Vaginal delivery is still possible in some cases after proper assessment and under close supervision. CS delivery is carried out to help with the birth process which is experiencing complications. Knowing the causal factors associated with cesarean delivery is expected to provide health education information to mothers to carry out routine antenatal care. Early detection of factors causing cesarean delivery in primigravida, as preparation for childbirth. Keywords: Caesarean section, logistic models, medical records, primigravidae